Molecular Dynamics Study on Complexation of Uranyl and Zinc Ions with Fatty Acid Bound Human Serum Albumin - Vijayakriti Mishra; Pramilla D. Sawant; Arup Kumar Pathak (Liquids)
Nuclear technology, while offering significant benefits across various sectors, poses potential health risks due to uranium (U) contamination, particularly through its internalization and subsequent interactions with biological systems. This study investigates the binding of uranyl (UO22+) and zinc (Zn2+) ions to Human Serum Albumin (HSA) that is already bound to fatty acids (FAs), using all-atom molecular dynamics (MD) simulations. The analysis focuses on the structural and dynamic alterations in the protein’s multi-metal binding site (MBS-A) caused by FA binding. Results reveal that FA binding induces a conformational change in HSA, disrupting the pre-formed MBS-A binding site, while still allowing uranyl and zinc ions to interact with residue D249 through strong Coulombic interactions. Secondary binding sites, associated with calcium and zinc binding, remain largely unaffected by FAs, providing alternative coordination for metal ions. This study also explores the binding and unbinding pathways of the metal ions using well-tempered meta-dynamics (WT-MtD), showing that while FA binding disrupts the primary metal binding site, it does not completely inhibit the binding of both uranyl and zinc ions. These findings offer new insights into the nature of uranium’s interactions with blood serum proteins and the role of fatty acids in modulating these interactions, which may help in designing future strategies for managing uranium contamination in biological systems.